2003
DOI: 10.4049/jimmunol.171.7.3359
|View full text |Cite
|
Sign up to set email alerts
|

Extrathymic TCR Gene Rearrangement in Human Small Intestine: Identification of New Splice Forms of Recombination Activating Gene-1 mRNA with Selective Tissue Expression

Abstract: Two new 5′-untranslated region (5′UTR) exons were identified in the human gene for the lymphocyte-specific endonuclease recombination activating gene-1 (RAG1) required for the somatic recombination yielding functional Ag receptors. These 5′UTR exons were used in three different splice forms by jejunal lymphocytes of the T cell lineage. RAG1 mRNA containing the previously described 5′UTR exon was not expressed in these cells. Conversely, one of the new 5′UTR exons was not expressed in thymus. The new RAG1 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…In addition, other reports have shown that the intestinal mucosa can act as sites for extrathymic maturation of T lymphocytes in humans [33,34] as well as in immunocompromized mice, e.g. TAP-deficient mice lacking MHC class I [34] and TcRab-deficient mice which under certain circumstances develop colitis [3,35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other reports have shown that the intestinal mucosa can act as sites for extrathymic maturation of T lymphocytes in humans [33,34] as well as in immunocompromized mice, e.g. TAP-deficient mice lacking MHC class I [34] and TcRab-deficient mice which under certain circumstances develop colitis [3,35].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, intestinal RAG expression has been recognized for a decade (1,4), although it is usually ascribed to CD8␣␣ cells. RAG expression has been reported in human intestine (12,34,35), specifically by immature CD3 Ϫ CD2 ϩ TCR Ϫ IEL and CD3 ϩ TCR Ϫ IEL (34) in the jejunum, and by immature CD3 Ϫ CD2 ϩ CD7 ϩ IEL and LPL in the small intestines of adults and children (35). It was recently reported that T cells in the human small intestine and bone marrow express two specific splice variants of the RAG-1 gene (1A/2 and 1A/1B/2) not found in thymocytes (35).…”
Section: Discussionmentioning
confidence: 99%
“…RAG expression has been reported in human intestine (12,34,35), specifically by immature CD3 Ϫ CD2 ϩ TCR Ϫ IEL and CD3 ϩ TCR Ϫ IEL (34) in the jejunum, and by immature CD3 Ϫ CD2 ϩ CD7 ϩ IEL and LPL in the small intestines of adults and children (35). It was recently reported that T cells in the human small intestine and bone marrow express two specific splice variants of the RAG-1 gene (1A/2 and 1A/1B/2) not found in thymocytes (35). It was proposed that T cells using the RAG-1 1A/2 and 1A/1B/2 variants migrate directly from the bone marrow to the small intestine, where they use the 1A/2-and 1A/1B/2-specific RAG-1 variants during TCR gene recombination in situ (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, intraepithelial lymphocytes located in the small intestinal mucosa were found to express recombination activating genes RAG 1, RAG 2 and pre-T a-chain, which are all required for T-cell receptor (TCR) rearrangement. [2][3][4] Although these findings strongly suggest the presence of extrathymic T-cell maturation (ETCM), no direct evidence of this phenomenon has been provided so far.…”
mentioning
confidence: 93%